The anthropometric characteristics and kinematic analysis of the cricket pull shot among Malaysian elite batsmen - Muhammad Zia Ul Haq Muhammad Aslam (N/A, 2017)
The anthropometric characteristics and kinematic analysis of the cricket pull shot among Malaysian elite batsmen by Muhammad Zia Ul Haq Muhammad Aslam